Analysis of clasp2 Transcription Pattern in Male Germ Cells during Spermatogenesis: A Comparative Study in Zebrafish (Danio rerio) and Guppy (Poecilia reticulata) - Serena Ricci; Maurizio Lazzari; Maria Gabriella Maurizii; Valeria Franceschini; Liliana Milani; Pietro Cacialli (Animals, 2023)
Cytoplasmic linker-associated protein-2 (CLASP2) is a member of the CLIP-associating proteins (CLASPs) family involved in the structure and function of microtubules and Golgi apparatus. Several studies performed using different mammalian and non-mammalian model organisms reported that CLASP2 controls microtubule dynamics and the organization of microtubule networks. In Drosophila and mice, an important role of CLASP2 during the development of germ cell lines has been uncovered. However, no study has clearly defined its role during fish germ cell differentiation. In the present study, we used two excellent aquatic animal models among teleost fish: zebrafish (Danio rerio) and guppy (Poecilia reticulata). Using qPCR, we found that the clasp2 transcript level is significantly high in the testis of both fish. Then, by in situ hybridization, we localized the clasp2 transcript in the spermatozoa of zebrafish and the spermatozeugmata of guppy. Our data suggest a potential role for this gene in the last stage of spermiogenesis in fish.